UPAYA PENGEMBANGAN AKOMODASI DAN TRANSPORTASI OBJEK WISATA ALAM MANDEH TARUSAN KABUPATEN PESISIR SELATAN - -, Devi - (Pendidikan Geografi, 2014)
Indonesia is a country that is a very interesting tourist attraction to visit for local and foreign tourists. In addition, tourism will get a lot of good material benefits for local government and the Indonesian government. The purpose of this study was to obtain data and information about accommodation and transportation development efforts natural attraction Mandeh Tarusan in South Coastal District.The research is a qualitative, research informants were taken by purposive sampling technique, with the research subject or respondent Department of Tourism, Head District of Koto XI Tarusan, Wali Nagari Mandeh, communities, and visitors in the surrounding natural attractions Mandeh Tarusan. Data were collected through observation and documentation of structured interviews. The data collected is to promote better accommodation and transportation of natural attractions.The results of this study concluded that: (1) the development of accommodation Mandeh Tarusan natural attractions such as inns, shops, and so on in this attraction is less. Because there is no donation from government to development this tourists area and also related with problem the status of land in tourists area community properties, so difficult development in tourism by government. (2) the development of tourist area transportations Mandeh Tarusan about transportations immediately to tourists area Mandeh Tarusan there is not. Public transport just arrived at the intersection near the base motorcycle towards the tourists area. Therefore the tourists who come tend to use private vehicles only. Suggestions for the author expected to the government to be concerned again about tourists area in Mandeh Tarusan, to advance local tourism.